Molecular and Physiological Characterization of Copper-Resistant Bacteria Isolated from Activated Sludge in an Industrial Wastewater Treatment Plant in Rungkut-Surabaya, Indonesia - WAHYU IRAWATI; TRIWIBOWO YUWONO; JOEDORO SOEDARSONO; HARI HARTIKO (Microbiology Indonesia, 2012)
Copper resistant bacteria can be isolated from environments where copper levels are abundant from mining, industrial, or agricultural activities. The aim of this work was to study the molecular and physiologicalcharacteristics of indigenous copper resistant bacteria isolated from activated sludge in an industrial wastewatertreatment plant in Surabaya, Indonesia. The bacterial isolates were designated as strains IrC1, IrC2, and IrC4. Phylogenetic analysis based on 16S rDNA sequence analysis identified isolates IrC1, IrC2, and IrC4 as Acinetobacter oleivorans (98.41% similarity), Acinetobacter pitii (97.22% similarity), and Cupriavidus pauculus (96.99 similarity), respectively. The addition of 5 mM of CuSO4 in the medium affected morphological 4 appearance of all isolates to green and undulate margin might be due to the survival mechanism of bacteria by absorbing the copper. This studies indicated that copper resistance mechanism of all isolates was facilitated through the bioaccumulation of copper inside the cell, especially on the membrane fraction and inside the cytoplasm, albeit at a limited amount. It was observed that isolates IrC1, IrC2, and IrC4 were capable of accumulating 137.23 , 364.66 , and 272.07 mg L-1 of copper, respectively from the medium containing 8 mM CuSO4. The capability of isolates IrC1, IrC2, and IrC4 to accumulate copper can be exploited in bioremediation 4 process for removing copper from industrial sewage.